All music guide to the blues : the experts' guide to the best blues recordings / edited by Michael Erlewine. - Erlewine, Michael (Backbeat Books, 1999)
Second edition of a guide to blues and gospel music, which features personal profiles of more than 700 singers and musicians, as well as discographies, reviews and charts. Also includes essays on the history and artistry of the blues.